A study on the perceptions on company’s social policy among employees in Syarikat Air Melaka Berhad (SAMB) / Kamalia Ibrahim - Ibrahim, Kamalia (Faculty of Business and Management, 2009)
The main purpose of this study is to identify level of intangible resources which is trust, responsibility and sense of belonging among employees at Syarikat Air Melaka Berhad and to find out the relationship between perceptions of company’s social policy and intangible resources. This study was using sample size of 150 respondents, at the Head Quarters of SAMB which located at Graha Maju. Primary and secondary data are using to get the information. The findings are interpreted using Statistical Package for Social Science (SPSS) program to analyze the data collected frequency and percent, descriptive statistics and correlation. Lastly conclusions was discussed in detail.